2018
DOI: 10.1017/s0033291718000612
|View full text |Cite
|
Sign up to set email alerts
|

Not urbanization level but socioeconomic, physical and social neighbourhood characteristics are associated with presence and severity of depressive and anxiety disorders

Abstract: These findings suggest that it is not population density in the neighbourhood, but rather the quality of socioeconomic, physical and social neighbourhood characteristics that is associated with the presence and severity of affective disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
88
2
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(98 citation statements)
references
References 78 publications
5
88
2
3
Order By: Relevance
“…Using genetically and environmentally wellcharacterized longitudinal data from a populationbased birth cohort, we therefore investigated (1) whether markers of the social environment at birth, including population density, deprivation, inequality, and social fragmentation were associated with positive and negative psychotic symptoms in adolescence; (2) whether PRS for schizophrenia were associated with social environments at birth; and (3) whether PRS for schizophrenia potentially confounded any associations between social environments at birth and positive or negative psychotic symptoms in adolescence. Consistent with available evidence, 21,29 we hypothesized that positive symptoms would be associated with greater population density at birth, and that deprivation and social fragmentation would be associated with both positive and negative symptoms.…”
Section: Introductionsupporting
confidence: 60%
See 1 more Smart Citation
“…Using genetically and environmentally wellcharacterized longitudinal data from a populationbased birth cohort, we therefore investigated (1) whether markers of the social environment at birth, including population density, deprivation, inequality, and social fragmentation were associated with positive and negative psychotic symptoms in adolescence; (2) whether PRS for schizophrenia were associated with social environments at birth; and (3) whether PRS for schizophrenia potentially confounded any associations between social environments at birth and positive or negative psychotic symptoms in adolescence. Consistent with available evidence, 21,29 we hypothesized that positive symptoms would be associated with greater population density at birth, and that deprivation and social fragmentation would be associated with both positive and negative symptoms.…”
Section: Introductionsupporting
confidence: 60%
“…54 Although the evidence linking the social environment to depression is more mixed than for psychosis, 55,56 a recent Dutch cross-sectional study found that neighborhood social characteristics, including low socioeconomic status and the proportion of people on benefits, were associated with rates of depression, but that population density was not. 29 In the ALSPAC sample, we have also previously shown that low levels of maternally reported neighborhood cohesion and high levels of neighborhood stress in childhood predict offspring depressive symptoms at age 18 years. 35 Our results, and other, 57 are compatible with the possibility that early social fragmentation may influence future risk of depression as well as psychosis.…”
Section: Comparison With Previous Studiesmentioning
confidence: 80%
“…In 3 aktuellen niederländischen Studien wurde der Zusammenhang zwischen Verkehrslärm und dem Vorhandensein von Depressionen und Angststörungen untersucht [28][29][30]. Leijssen et al zeigten, dass Straßenverkehrslärmexposition mit erhöhter Wahrscheinlichkeit einer bestehenden depressiven Verstimmung einhergeht (n = 23 293; OR 1,65; 95 %-KI 1,10-2,48 beim Vergleich von ≥ 70 vs. 45-54 dB(A) L den ), die unabhängig von ethnischen und sozioökonomischen Ungleichheiten zwischen den Expositionsgruppen war [28].…”
Section: Lärmbelästigungunclassified
“…In einer Studie (n = 2980) von Generaal et al war Verkehrslärm mit einer OR von 1,26 (95 %-KI 1,08-1,47) für das Vorhandensein einer Depression bzw. mit einer OR von 1,29 (95 %-KI 1,11-1,50) für eine bestehende Angststörung pro Zunahme um 3,21 dB(A) L den assoziiert [29]. Die gepoolte Analyse von 8 niederländischen Kohortenstudien (n = 32 487) ergab eine OR von 1,05 (95 %-KI 0,96-1,15) für den Zusammenhang zwischen Verkehrslärm und einer prävalenten Depression, wobei hier kritisch angemerkt werden muss, dass in der Hälfte der eingeschlossenen Studien die Bestimmung der Verkehrslärmpegel 1-2 Jahre später erfolgte als die Erfassung der Depression [30].…”
Section: Lärmbelästigungunclassified
“…1 In addition to research on individual-level risk factors, growing attention is being paid to the wider determinants of mental health inequalities. Research has shown that the urban environment is linked with common mental disorders 2 and psychotic illnesses, 3 and this relationship may be explained by local differences in both social and physical conditions, 4 including income deprivation, crime, or social cohesion. 5−7 Although most of the research on contextual risks is focused on the association with area-based poverty, evidence is more limited regarding the causal pathways linking neighborhood deprivation to mental disorders.…”
mentioning
confidence: 99%